Systematic critical review of previous economic evaluations of smoking cessation during pregnancy - Jones, Matthew; Lewis, Sarah; Parrott, Steve; Coleman, Tim (BMJ Publishing Group Ltd, 2015)
Objective: To identify and critically assess previous economic evaluations of smoking cessation interventions delivered during pregnancy.